The transmission of agricultural knowledge among members of The Mulya Tani Farmer Group in Sipanjang Hamlet - Lujeng Lutfi Fauziah; Harto Wicaksono (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Knowledge inheritance is a crucial component of sustaining agricultural practices amidst modernization. This study examines the role of farmer groups in the transmission of farming culture and the system of cultural knowledge inheritance among members of the Mulya Tani Farmer Group in Sipanjang Hamlet. This study employs a qualitative methodology with an ethnographic approach to explore and comprehend farming culture through behavioral patterns and interactions within the farming community of Sipanjang Hamlet. Data were collected through observations, interviews, and documentation. The findings indicate that the transmission of farming knowledge among farmers persists, evolving from traditional local knowledge to incorporating elements of agricultural modernization into the training. Farmer groups introduce new knowledge, resulting in a shift in traditional practices. The integration of modern and local knowledge in farming practices encompasses aspects such as knowledge, farming techniques, tools, technologies, and traditions. The transmission of farming cultural knowledge is facilitated by three preservation aspects: protection, development, and utilization. Agricultural modernization is associated with capitalization through government extension programmes. However, local traditions remain intact, as commercialization does not undermine the knowledge system. The transmission of farming cultural knowledge serves not only economic purposes but also supports the preservation of local knowledge and agricultural sustainability.   Pewarisan pengetahuan menjadi aspek penting dalam upaya menjaga keberlanjutan praktik pertanian di tengah era modernisasi. Penelitian ini bertujuan untuk menganalisis peran kelompok tani dalam pewarisan budaya bertani dan sistem pewarisan pengetahuan budaya bertani pada petani Kelompok Tani Mulya Tani di Dusun Sipanjang. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan etnografi sebagai pendekatan untuk menggali dan memahami budaya bertani melalui pola perilaku dan interaksi pada masyarakat petani Dusun Sipanjang. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian menunjukkan bahwa pewarisan pengetahuan bertani pada petani  dilakukan hingga sekarang dengan dinamika pengetahuan bertani dari yang sebelumnya berupa pengetahuan lokal hingga masuknya modernisasi pertanian. Kehadiran kelompok tani membawa kebaharuan pengetahuan dan adanya pergeseran pengetahuan lama. Pewarisan praktik bertani seiring modernisasi pertanian mengintegrasikan pengetahuan modern dan pengetahuan lokal yang meliputi aspek pengetahuan, teknik bertani, alat, teknologi dan tradisi. Pewarisan pengetahuan budaya bertani melalui tiga aspek pelestarian, yaitu perlindungan, pengembangan, dan pemanfaatan. Modernisasi pertanian memiliki keterkaitan dengan kapitalisasi melalui program penyuluhan oleh pemerintah. Akan tetapi, aspek pengetahuan berupa tradisi lokal tidak digantikan sebab komersialisasi tidak menyerang sistem pengetahuan tersebut. Pewarisan pengetahuan budaya bertani tidak hanya sekedar untuk kepentingan mendapatkan keuntungan secara ekonomi, tetapi juga mendukung menjaga kelestarian pengetahuan lokal dan keberlanjutan pertanian.